Policy, Profits, and Palm Oil: A Bibliometric Synthesis of the Economic and Environmental Payoffs - Judijanto, Loso; Bunyamin, Ilham Akbar; Lesmana, Tera (Westscience Press, 2025)
The global palm oil industry sits at the nexus of economic growth and environmental sustainability, generating both substantial financial returns and significant ecological concerns. This study presents a bibliometric synthesis of scholarly literature on palm oil, with particular focus on the interplay between policy frameworks, profitability, and environmental outcomes. Using the Scopus database, a total of relevant publications from 2000 to 2024 were analyzed through VOSviewer software to identify trends in co-authorship, citation patterns, and keyword co-occurrence. The findings reveal that